Agama dan Entertainment: Fungsi Sosial Media Massa dalam Program Religi di TV - Monika Sri Yuliarti (Program Studi Ilmu Komunikasi, 2011)
Mass media have four social functions. They are surveillance, correlation, socialization (transmission of values), and entertainment (Lasswell & Wright in Dominick, 2005). A good mass media product is supposed to fulfill all those functions. So is the television program. A good television program must include four social functions of the mass media in balance. This article will highlight the religious program on Indonesian television that has been growing recently. Several religious programs on 11 television stations (state and private stations) have been observed and results that the religious programs, whether in a talk show or soap opera format, accentuate entertainment function more in comparison with other functions.